United States : Information Note on the United States' Fiscal Data. (IMF Staff Country Reports; Country Report ;, 2007)
This paper reports on a pilot study to present the United States fiscal data in a manner consistent with the Government Finance Statistics Manual (GFSM 2001). The study incorporates cash and accrual source data in a consistent and harmonized statistical framework, enhancing the accuracy and transparency of fiscal data. The paper presents a general discussion of the source data and the institutional coverage used in the U.S. pilot study. It describes the main results of the pilot, and suggests further work to improve the fiscal statistics in accordance with the GFSM 2001 framework.